Comparison between the seventh and eighth edition of the AJCC/UICC staging system for nasopharyngeal cancer integrated with pretreatment plasma Epstein–Barr virus DNA level in a non-Chinese population: secondary analysis from a prospective randomized trial. (23rd July 2019) - Kitpanit, Sarin; Jittapiromsak, Nutchawan; Sriyook, Aniwat; Prayongrat, Anussara; Kannarunimit, Danita; Chakkabat, Chakkapong; Lertbutsayanukul, Chawalit
Abstract : The eighth AJCC/UICC staging for nasopharyngeal cancer had higher prognostic values than the previous edition. Pretreatment plasma EBV DNA integrated into the next edition could further improve the outcome prediction. Abstract: Objective: To validate the eighth edition of the AJCC/UICC staging system in nasopharyngeal cancer (NPC) patients who were uniformly treated in a prospective randomized study using intensity-modulated radiation therapy and to investigate the prognostic value of plasma Epstein-Barr virus (EBV) DNA level when incorporated into the TNM staging. Methods: Between October 2010 and September 2015, non-metastatic NPC patients were treated with concurrent chemoradiation followed by adjuvant chemotherapy. Pretreatment images of 205 patients were reviewed by two radiologists to determine the TNM classification according to the seventh and eighth editions of the AJCC/UICC staging system. Overall survival (OS), progression-free survival (PFS) and distant metastasis-free survival (DMFS) were calculated. Harrell's C concordance index (C-index) and Akaike information criterion (AIC) were used to compare the staging models. Recursive partitioning analysis (RPA) was conducted and incorporated with plasma EBV DNA. Results: Overall, the eighth edition showed higher C-indexes and lower AIC values in nodal classification and stage groups, indicating a better discrimination performance and better goodness of fit, but showed similar separation for T classification compared with the seventh edition. The integration of pretreatment EBV values (<2300 vs ≥2300 copies/ml) to the eighth edition AJCC/UICC staging system allowed the classification of patients into three RPA categories and further lowered the AIC value and increased the C-index for OS. Conclusion: The eighth edition of the AJCC/UICC staging system had higher prognostic values in terms of OS, PFS and DMFS than the previous edition. An integration of pretreatment plasma EBV DNA into the next AJCC/UICC staging could improve the outcome prediction especially in poor risk groups who might benefit from treatment intensification.